Deletion of steroid 5α-reductase 2 gene in male pseudohermaphroditism - Andersson, Stefan (Nature, 1991)
The conversion of testosterone into dihydrotestosterone by steroid 5α-reductase is a key reaction in androgen action, and is essential both for the formation of the male phenotype during embryogenesis and for androgen-mediated growth of tissues such as the prostate(1,2). Single gene defects that impair this conversion lead to pseudohermaphroditism in which 46 X, Y males have male internal urogenital tracts, but female external genitalia(3). We have described the isolation of a human 5α-reductase complementary DNA from prostate(4). Subsequent cloning and genetic studies showed that this gene (designated 5α-reductase 1) was normal in patients with 5α-reductase deficiency(26). We report here the isolation of a second 5α-reductase cDNA by expression cloning and the polymerase chain reaction. The biochemical and pharmacological properties of this cDNA-encoded enzyme (designated 5α-reductase 2) are consistent with it being the major isozyme in genital tissue. A deletion in this gene is present in two related individuals with male pseudohermaphroditism caused by 5α-reductase deficiency. These results verify the existence of at least two 5α-reductases in man and provide insight into a fundamental hormone-mediated event in male sexual differentiation.